Crisis Region Western Africa - The cradle of African migration to Europe - Dirk Kohnert (Africa and Fortress Europe - Threats and opportunities, 2007)
In the last decades the number of refugees from conflict regions in Africa increased dramatically. West Africa is the cradle of migration from Sub-Saharan Africa to Europe, were most African migrants with overseas destinations live. The European Union shares dual responsibility for the continuing migration pressure: First, because they fostered over decades corrupt and autocratic regimes with dire disregard to principles of "good governance". The aftermath of these regimes is still to be felt today, and constitutes one of the underlying factors for politically motivated migration. Secondly, the EU contributed to Africa's growing economic misery, due to the damaging effects of European selfish external trade policy. Nevertheless, the prevailing perspective of the EU concerning African immigration remains to be focused on security, the foreclosure of its external borders and prevention. Current EU programs to combat African migration by development orientated instead of adequate immigration policies is bound to fail, according to available evidence and literature. The drain of human capital from Africa is most pronounced in the employment sector for highly qualified personnel. Another remarkable trend is the "feminization" of the brain drain in recent years, caused by the growing number of highly skilled African women looking for employment abroad. However, migration is not necessarily a zero-sum game. There are also positive - although often neglected - economic and socio-cultural effects of the brain drain. Remittances of African migrants contribute considerably not just to the wellbeing of their extended families at home, but to poverty reduction and development on a national level in general. They constitute the second largest source of external private finance, besides foreign direct investment. In addition, a counteracting "brain gain", i.e. new value systems, political and spiritual orientations, acquired by migrants in Europe, results in a transfer of knowledge and of innovations. – – La région de crise ouest africaine - Le berceau de la migration africaine vers l'Europe : Dans les dernières décennies, le nombre de réfugiés en provenance de zones de conflit en Afrique a augmenté de façon spectaculaire. Afrique de l'Ouest est le berceau de la migration de l'Afrique subsaharienne vers l'Europe. L'Union européenne partage une double responsabilité pour la pression migratoire continue: d'abord, parce qu'elle a tolérée au cours des décennies la corruption et des régimes autocratiques au mépris des principes de «bonne gouvernance». L'impact néfaste de ces régimes se ressent jusqu'à ce jour. Il constitue l'un des facteurs sous-jacents de la migration politiquement motivée. Deuxièmement, l'UE a contribué à la misère économique croissante de l'Afrique, en raison des effets néfastes de la politique européenne du commerce extérieur égoïste. Néanmoins, la perspective dominante de l'UE concernant l'immigration africaine reste à être axée sur la sécurité, la forclusion de ses frontières extérieures et la prévention. Les programmes actuels de l'UE pour lutter contre la migration africaine par l'aide au développement à la place d'une politique d'immigration appropriés est vouée à l'échec, selon les éléments de preuve et de la littérature disponible. Le drain du capital humain de l'Afrique est le plus prononcé dans le secteur de l'emploi de personnel hautement qualifié. Une autre tendance remarquable est la «féminisation» de la fuite des cerveaux dans les dernières années, causé par le nombre croissant de femmes africaines hautement qualifiés à la recherche d'emploi à l'étranger. Toutefois, la migration est pas nécessairement un jeu à somme nulle. Il y a aussi des effets économiques et socio-culturels positif - bien que souvent négligés - de la fuite des cerveaux. L'envois de fonds des migrants africains contribuent considérablement non seulement pour le bien-être de leurs familles élargies, mais à la réduction de la pauvreté et le développement au niveau national en général. Ils constituent la deuxième source de financement privé externe, en plus de l'investissement étranger direct. En outre, un "gain de cerveaux" opposé, à savoir des nouveaux systèmes de valeurs, des orientations politiques et spirituels, acquis par les migrants en Europe, va résulter dans un transfert de connaissances et d'innovations.
Additional information: Author's version
Keywords: F22; F35; F42; F53; N17; N37; N44; O15; O2; R23; 330; Migration; West Africa; Europe; brain-drain; circular migration; remittances; foreign aid; EU trade policy; Migranten; Subsahara-Afrika; EU-Außenwirtschaftspolitik; Entwicklungshilfe